Hypersensitivity to material and environmental burden as a possible cause of late complications of cardiac implantable electronic devices - Manoušek, Jan; Andršová, Irena; Stejskal, Vera; Vlašínová, Jitka; Sepši, Milan; Kuta, Jan; Klánová, Jana; Mazík, Michal; Jarkovský, Jirí; Šnajdrová, Lenka; Benešová, Klára; Novotný, Tomáš; et al. (Europace, 2018)
AIMS: To evaluate whether patients with late complications of pacemakers or implantable cardioverter-defibrillators have hypersensitivity reactions to some of the materials used in generators or in electrodes, or to environmental metal burden. METHODS AND RESULTS: The cohort consisted of 20 men and 4 women (mean age: 62.3 ± 17.2 years) who had a history of late complications of implanted devices. The control group involved 25 men and 8 women (mean age: 64.6 ± 14.0 years) who had comparable devices, but no history of late complications. Lymphocyte transformation test was used to evaluate hypersensitivity to eight metal pollutants (antimony, manganese, mercury, molybdenum, nickel, platinum, tin, and titanium) selected by results of questionnaires on environmental burden, and by material analysis of generators and electrode surfaces. Exposures to metal pollutants were approximately the same in patients and in controls. Titanium alloy used in generators contained at least 99.32% of titanium and trace levels of other metals; higher levels of tin and platinum were detected in electrode surfaces. Hypersensitivity reactions to mercury and tin were significantly more frequent in patients than in controls (patients and controls: mercury: 68.2 and 31.1%, respectively; P = 0.022; tin: 25.0 and 3.2%, respectively; P = 0.035). In contrast, hypersensitivity to manganese was significantly more frequent in controls than in patients (patients and controls: 13.6 and 50.0%, respectively; P = 0.008). CONCLUSION: Our findings suggest a possible relation between hypersensitivity to metals used in implantable devices or to environmental metal burden and the occurrence of their late complications.
Keywords: Mercury; infekce spojené s protézou; Antimony; Humans; mangan; Prosthesis Implantation; Alloys; Metals; lidé středního věku; pooperační bolest; Skin Diseases; alergie; Tin; Platinum; molybden; Female; Aged; antimon; Hypersensitivity; implantace protézy; senioři; lidé; kovy; Cardiac Resynchronization Therapy Devices; Prosthesis-Related Infections; Lymphocyte Activation; titan; látky znečišťující životní prostředí; Postoperative Complications; nikl; Environmental Pollutants; aktivace lymfocytů; pooperační komplikace; ženské pohlaví; kožní nemoci; Manganese; Male; Titanium; Middle Aged; Molybdenum; Nickel; defibrilátory implantabilní; cín; slitiny; Pain, Postoperative; prostředky srdeční resynchronizační terapie; mužské pohlaví; platina; rtuť; Defibrillators, Implantable